IFIS - International Food Information Service - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1988)
In 1968 food science and technology lacked a voice to acquaint a world just coming to the realization that food supply was unlikely to meet the demand of a global population which would double by the year 2000 with this emerging and vital...